Screen printed ZnO thick films for NH3 gas sensing. Issue 1 (1st October 2022) - Salunke, Vaishali T.; Buchade, P.B.; Shaligram, A.D.; Borse, R.Y.
Abstract : The paper reports the synthesis of ZnO powder by self-propagation solution combustion method and the development of screen-printed ZnO thick films for sensing ammonia gas. The surface and structural examination of the thick film was studied by using SEM and XRD techniques. The particle and grain size of the thick film were determined using SEM and XRD respectively. The temperature coefficient of resistance (TCR), electrical, and NH3 gas sensing characteristics of ZnO thick film were observed with varying temperatures. Thick films show the inverse relations of resistance with respective temperatures. The sensitivity, response, and recovery time toward NH3 gas sensing were discussed.